Analysis of selected parking spaces in medium sized cities of tamil nadu - R. Prasannakumar, Dr; Naga sai baba, Akella.; Ranjith Kumar, V; R, Sudharsan. (International Journal of Engineering and Technology, 2018)
The present study aims to analyze the conditions of identified parking lots in two medium sized cities of Tamil Nadu, namely Tiruchirapalli and Thanjavur, and suggest possible measures for improvement. Methods like parking space inventory survey, cordon count and parking usage control by patrol were used for data collection. The number of vehicles occupying the parking spaces at a specific period of time was determined. This count was taken at regular intervals over a time period spread over 9 am to 6 pm, in three sessions. The data collected was then analysed and peak values of the numbers of different types of vehicles was identified. Observations of the prevalent topographical conditions at the study locations were made and a few suggestions pertaining to maintenance, enhancement, improved efficiency and tariff were provided. Â Â